Fertilization failure after IVF in 304 couples—A case-control study on predictors and long-term prognosis. (January 2015) - Krog, Maria; Prior, Maria; Carlsen, Elisabeth; Loft, Anne; Forman, Julie; Pinborg, Anja; Andersen, Anders Nyboe
Abstract: Objectives: To identify predictors of total fertilization failure (TFF) and thereby optimize the primary allocation of patients with no well-defined male factor to either IVF or intracytoplasmatic sperm injection (ICSI). Further, to evaluate the long-term fertility prognosis of couples experiencing TFF. Study design: A retrospective case-control study including 304 couples with TFF and 304 controls with fertilization after IVF during a 10-year period from year 2000–2010. The controls were the patients with minimum one fertilized oocyte just prior to the cases. Multiple logistic regression analysis was used to evaluate the predictors of TFF. Results: The multiple regression analysis identified the following independent predictors of TFF: female smoking, adjusted odds ratio (AOR) 1.7 (95% CI 1.1–2.3), non-tubal factor AOR 2.2 (95% CI 1.5–3.4), progressive motile spermatozoa after preparation × 10 6 /ml (Log 2 scale) AOR 1.4 (95% CI 1.2–1.6). For every oocyte, decreasing from four to one oocytes, the risk of TFF increased with AOR 2.0 (95% CI: 1.5–2.9) and from seven to four oocytes with AOR 1.2 (95%CI: 1.0–1.3), respectively. In case of more than seven oocytes the risk of TFF did not vary significantly by the number of oocytes. Female age, BMI, duration of infertility, earlier natural or IUI conceptions were not predictors of TFF. After a minimum of 30 months of follow-up from the index cycle, 50% of the TFF patients succeeded in a live childbirth compared with 70% of the controls. Only thirty five percent of the total number of births in the TFF patients was after ICSI. Conclusion: The risk of TFF is associated with the number of available oocytes for fertilization, female smoking, non-tubal factor infertility and an apparently minor sperm factor. However, anticipated predictors like advanced female age, duration of infertility and earlier conceptions proved not to have any predictive value. Couples experiencing TFF have a significantly reduced overall long-term chance of live birth compared with controls.